Pengaruh Kesejahteraan Psikologis terhadap Kinerja Guru dalam Konteks Tenaga Kependidikan di Sekolah: Penelitian - Sep Arinda Risa Kamal; Yosi Imas Kristiyana; Siti Zulaikha; Muhammad Takdir (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to systematically analyze the influence of psychological well-being on teacher performance within the context of educational staff in schools. Utilizing a systematic literature review (SLR) method based on PRISMA guidelines, this study identifies, evaluates, and synthesizes findings from various relevant scientific publications. The review results indicate that psychological well-being has a positive and significant influence on teacher performance, encompassing aspects of instructional planning, implementation, and assessment, as well as professional development and interpersonal relationships. This relationship is mediated by factors such as professional commitment, job satisfaction, and motivation, and moderated by organizational support, workload, psychological capital, and demographic characteristics. These findings affirm that psychological well-being is relevant not only for teachers but also for all educational staff, who collectively contribute to the effectiveness of the school ecosystem. Practical implications include the formulation of policies supporting the well-being of educational staff, the development of intervention programs, and the creation of a supportive work environment to enhance overall educational quality.